If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(4z + 7) + -4(2 + -5) = 0 Reorder the terms: 2(7 + 4z) + -4(2 + -5) = 0 (7 * 2 + 4z * 2) + -4(2 + -5) = 0 (14 + 8z) + -4(2 + -5) = 0 Combine like terms: 2 + -5 = -3 14 + 8z + -4(-3) = 0 Multiply -4 * -3 14 + 8z + 12 = 0 Reorder the terms: 14 + 12 + 8z = 0 Combine like terms: 14 + 12 = 26 26 + 8z = 0 Solving 26 + 8z = 0 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-26' to each side of the equation. 26 + -26 + 8z = 0 + -26 Combine like terms: 26 + -26 = 0 0 + 8z = 0 + -26 8z = 0 + -26 Combine like terms: 0 + -26 = -26 8z = -26 Divide each side by '8'. z = -3.25 Simplifying z = -3.25
| 8x=-11y-16 | | 7*12+5= | | 124-(6x+16)=6(x+5)+x | | 3(3y-1)=6y | | 6p^2=-23p-15 | | 3(-4)(-6)= | | 6.4x-2.3x=73.8 | | 3(3r+5)-2(r+4)= | | -10n+16=-6n-12 | | 5.5x=55.0 | | 5(x+3)--7= | | 5x-4y=-26 | | x=3y-14 | | 5y=4(y+6) | | x+4/5=3 | | 3x=2(x+5)answer | | 35*(x-2)= | | 0=-4x^2+9x+3 | | 0=-2x^2+5x+3 | | 72-(5x+15)=5(x+7)+x | | 0=-3x^2+7x+2 | | -l-19l-l-23-2l= | | 4.3333333x+4=1.5x+3 | | 3p^2=-8p-4 | | 4c^2+21c+27=0 | | 3x-6=2-x | | 3x-6=2-4 | | x-3=2x-2 | | -24+14=m | | -5r-7r+2=5r-r | | 7(x-3)=4x+5 | | z+3(z-1)-2-3(z-1)=0 |